Visitors' satisfaction and evaluation to walk on the trails of forest: evidence from the national forest of Akasawa, Japan. Issue 1 (December 2020) - Zhang, T; Deng, S Q; Gao, Y; Zhang, Z; Meng, H; Zhang, W K
Abstract: In the recent decade, people's interest for forests has increased tremendously throughout the globe. So, providing good forest landscape space to visitors has become an important issue for the landscape designers. Because, good forest resource planning and development can not only drive the sustainable development of the forest industry, but also its ripple effect can induce improvement in agricultural industry and economy in the region. The present study identified the evaluative behaviors among visitors walking on the trails of Akasawa national recreational forest, the birthplace of forest bathing in Japan. The study determined the factors that influenced the satisfaction rates of the visitors. The significance of this study is not only to improve the planning and design of the forest space itself, but also to provide theoretical guidance for the planning of the regional landscape of the rural areas attached to it. The study results revealed, visitors' subjects for evaluation changed with the surrounding environment. While visitors appreciated large-scale landscape elements, such as "large-size trees" and "buttress roots" within coniferous forests. They valued small-scale landscape elements such as "flowering plants" within broad-leaved or mixed forests. Another important issue came out as a result of the present study is that the light and dark changes in the forest walking trail can continuously awaken the evaluation behavior of tourists. In this study visitors displayed evaluative behaviors most frequently on the Mukaiyama Course. It is rich in different types of forest stands and has variance illumination levels. Factors that influence the satisfaction rates of visitors were "landscape", "vegetation", "trail condition" and "ease of walking". Factors that influence the frequency of evaluative behaviors included "landscapes" surrounding the trails and "ease of walking". Through this study we can see that when we need to plan the forest spatial walking trails, it is very necessary to consider small-scale landscape elements, rich in different types of forest stands with varying illumination levels.